The Effectiveness of Blended Learning on Learners’ Interaction and Satisfaction - Hariharan N Krishnasamy, Nurul Imtiaz Abd Gani, Mohan A/L Rathakrishnan, (Opción, 2019)
This study examines the effectiveness of Blended Learning in the form of lecturer-learner, learner-learner and learner-course materials interaction with learners’ satisfaction in an English Proficiency course. Both qualitative and quantitative methods will be used to conduct this study at the Higher Education Institution (HEI). As a result, Learner to course materials interaction means that learners need to interact, digest and learn the course content that they receive from an expert. In conclusion, universities are paying serious attention to low satisfaction among learners because it may give universities a negative image and indirectly affect learners’ enrolment to that particular university.